A hybrid mutation artificial bee colony algorithm for spectrum sharing. (2018) - Huang, Ling; Liu, Jiaqi; Guo, Lin
In order to alleviate the spectrum scarcity problem in wireless networks, achieve efficient allocation of spectrum resources and balance the users' permission to spectrum, a hybrid mutation artificial bee colony algorithm based on the artificial bee colony algorithm is presented. The presented algorithm aims to enhance the efficiency of global searching by improving the way of leaders searching the nectar source with differential evolution algorithm. In addition, the onlookers' searching method is improved by bat algorithm to guarantee the convergence efficiency of the algorithm and the precision of the result and it is assumed that the onlookers are equipped with bats' echolocation to get close to the nectar source by adjusting the rate of pulse emission and loudness when they are searching nectar source. The simulation results show that the proposed algorithm has faster convergence, higher efficiency and more optimal solutions compared with other algorithms.